Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms23073727
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Populus euphratica under Salt Treatment and PeERF1 Gene Enhances Salt Tolerance in Transgenic Populus alba × Populus glandulosa

Abstract: Populus euphratica is mainly distributed in desert environments with dry and hot climate in summer and cold in winter. Compared with other poplars, P. euphratica is more resistant to salt stress. It is critical to investigate the transcriptome and molecular basis of salt tolerance in order to uncover stress-related genes. In this study, salt-tolerant treatment of P. euphratica resulted in an increase in osmo-regulatory substances and recovery of antioxidant enzymes. To improve the mining efficiency of candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Currently, various omics techniques have become an effective strategy to better understand the response mechanisms to environmental stresses such as salt stress ( Dai et al., 2022 ). In recent years, there have been many reports on the study of salt tolerance in plants through transcriptomic approaches ( Chen et al., 2022a ; Ge et al., 2022 ; Wang et al., 2022a ; Xu et al., 2022 ). Recently, metabolomic studies on salt tolerance in plants have reported that increased accumulation of metabolites and related pathways that mainly regulate the antioxidant defense system in different Indian mustard ( Brassica juncea ) varieties under different periods of salt stress give the high-yielding variety CS60 an advantage over CS245-2-80-7 and may be the main tolerance mechanism for its resistance to salt stress ( Singh et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various omics techniques have become an effective strategy to better understand the response mechanisms to environmental stresses such as salt stress ( Dai et al., 2022 ). In recent years, there have been many reports on the study of salt tolerance in plants through transcriptomic approaches ( Chen et al., 2022a ; Ge et al., 2022 ; Wang et al., 2022a ; Xu et al., 2022 ). Recently, metabolomic studies on salt tolerance in plants have reported that increased accumulation of metabolites and related pathways that mainly regulate the antioxidant defense system in different Indian mustard ( Brassica juncea ) varieties under different periods of salt stress give the high-yielding variety CS60 an advantage over CS245-2-80-7 and may be the main tolerance mechanism for its resistance to salt stress ( Singh et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The selection and identification of appropriate targets are essential for the genetic modification and molecular breeding of salt-resistant poplars [5]. The transcriptional regulation of salt-responsive genes in Populus euphratica (a salt-tolerant poplar species) is critical for these plants to mediate ionic and ROS homeostasis and for their adaptation to a salt environment [6][7][8][9][10][11][12][13][14][15][16][17]. Glycine-rich RNA-binding proteins (GRPs) interact with target mRNAs in the nucleus and regulate the processing and folding of the mRNAs [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a salt-tolerant chlorophyll gene, PeCLH2 , was identified through transcriptome analysis of P. euphratica in the early stage, and heterologous expression of the PeCLH2 gene was performed in P. alba × P. glandulosa [ 27 , 28 ]. Transcriptome analyses were performed on overexpression, RNA interference expression and wild-type plants.…”
Section: Introductionmentioning
confidence: 99%